2010
DOI: 10.1096/fj.09-149518
|View full text |Cite
|
Sign up to set email alerts
|

NHE1 promotes invadopodial ECM proteolysis through acidification of the peri‐invadopodial space

Abstract: Extracellular matrix (ECM) degradation is a critical process in tumor cell invasion and requires membrane and released proteases focalized at membrane structures called invadopodia. While extracellular acidification is important in driving tumor invasion, the structure/function mechanisms underlying this regulation are still unknown. Invadopodia are similar in structure and function to osteoclast podosomes responsible for bone degradation, and extracellular acidification is central to podosome action, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
192
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(200 citation statements)
references
References 64 publications
8
192
0
Order By: Relevance
“…Caveolae have been shown to contain NHE1 in other types of cells (Tekpli et al, 2008) and, independently, to be involved in breast cancer cell invasiveness (Yamaguchi et al, 2009). Recently, it has been shown that NHE1 is localized in invadopodia where it is responsible for an extracellular acidification and the degradation of the extracellular matrix (Busco et al, 2010). Our study brings a new mechanistic explanation for caveolae involvement in cancer cell invasiveness.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Caveolae have been shown to contain NHE1 in other types of cells (Tekpli et al, 2008) and, independently, to be involved in breast cancer cell invasiveness (Yamaguchi et al, 2009). Recently, it has been shown that NHE1 is localized in invadopodia where it is responsible for an extracellular acidification and the degradation of the extracellular matrix (Busco et al, 2010). Our study brings a new mechanistic explanation for caveolae involvement in cancer cell invasiveness.…”
Section: Resultsmentioning
confidence: 58%
“…Na v 1.5 promotes NHE1-dependent invasiveness L Brisson et al cells to adapt to their high metabolic H þ production (Gatenby et al, 2007). Indeed it has been shown to have a predominant role in extracellular acidification of tumor cells (Bourguignon et al, 2004) and also to be involved in their invasive process (Cardone et al, 2005;Stock and Schwab, 2009;Busco et al, 2010). In this study, we showed for the first time the evidence that Na V 1.5 channels, abnormally expressed in breast cancer cells, functionally interact with NHE1 in caveolae to enhance its H þ -efflux activity and consequently promote acidic-dependent invasion of the extracellular matrix.…”
Section: Resultsmentioning
confidence: 99%
“…These proteolytic enzymes digest a path through the extracellular matrix allowing for cells to leave the primary tumour and enter the bloodstream [24,25]. It is also of note that elevated NHE1 activity contributes of sodium loading of cells.…”
Section: Discussionmentioning
confidence: 99%
“…NHE1 activity acidifies the peri-invadopodial space, establishing the optimal pH for the proteolytic activity of serine proteases and matrix metalloproteinases that aid in the digestion of extracellular matrix at the leading edge of invading cells (75,76) Of all the mutations to NHE1, though, S703A was the most remarkable. Cells expressing S703A-NHE1 exhibited a drastic change in morphology, seemingly reverting from their characteristic mesenchymal morphology to a more epithelial-like phenotype.…”
Section: Beyond "Housekeeping": Nhe1's Definitive Role In Triple-negamentioning
confidence: 99%